Last Best Chance Michael Kaiser talks - Robertson, Allen (Dance Books Ltd., Alton,Hampshire (UK), 1999)
Michael Kaiser, chief executive of the Royal Opera House talks. PALABRAS CLAVE: Michael Kaiser, Royal Opera House, interview.